Mean-field description of a dynamical collapse of a fermionic condensate in a trapped boson-fermion mixture - Adhikari, Sadhan K. [UNESP] (American Physical Society (APS), 2004)
The collapse dynamics of fermions in a boson-fermion mixture using a coupled time-dependent mean-field-hydrodynamic model, was investigated. The collapse was considered with an increase in number of bosonic atoms, and an increase of the attractive boson-fermion interaction using a Feshbach resonance. Under high pressure, three-body recombination took place with the emission of energy leading to explosion and loss of atoms. The results show that under different situations, the fermionic component in a trapped condensed boson-fermion mixture can undergo a collapse due to an attractive boson-fermion interaction.